الخصائص الفنية للقصة القصيرة جدًا في المجموعة القصصية - غمام اعمارة رحمة; بدادة بسمة; غمام علي الشيماء; هديل لعسل (University of Eloued جامعة الوادي, 2025)
We have talked in this research topic about the subject of the very short story. If we dealt with the theoretical side in the first section the concept of the very short story and its origin and development in the West and the Arabs, as for the second section we dealt with the issue of the overlap of genres and in the practical side we took the collection of short stories before that by Al-Saeed Abu Naasa as a model for the application of the very short characteristics if the collection of short stories before that carried several functions that reflected to us the beauty of the texts.
مذكرة ليسانس.دراسات ادبية.2025
Keywords: الخصائص الفنية -القصة القصيرة – المجموعة القصصية Technical characteristics - short story - short story collection